Drivers of care costs and quality in the last 3 months of life among older people receiving palliative care: A multinational mortality follow-back survey across England, Ireland and the United States. (April 2020) - Yi, Deokhee; Johnston, Bridget M; Ryan, Karen; Daveson, Barbara A; Meier, Diane E; Smith, Melinda; McQuillan, Regina; Selman, Lucy; Pantilat, Steven Z; Normand, Charles; Morrison, R Sean; Higginson, Irene J
Background: Care costs rise towards the end of life. International comparison of service use, costs and care experiences can inform quality and improve access. Aim: The aim of this study was to compare health and social care costs, quality and their drivers in the last 3 months of life for older adults across countries. Null hypothesis: no difference between countries. Design: Mortality follow-back survey. Costs were calculated from carers' reported service use and unit costs. Setting: Palliative care services in England (London), Ireland (Dublin) and the United States (New York, San Francisco). Participants: Informal carers of decedents who had received palliative care participated in the study. Results: A total of 767 questionnaires were returned: 245 in England, 282 in Ireland and 240 in the United States. Mean care costs per person with cancer/non-cancer were US$37, 250/US$37, 376 (the United States), US$29, 065/US$29, 411 (Ireland), US$15, 347/US$16, 631 (England) and differed significantly ( F  = 25.79/14.27, p  < 0.000). Cost distributions differed and were most homogeneous in England. In all countries, hospital care accounted for > 80% of total care costs; community care 6%–16%, palliative care 1%–15%; 10% of decedents used ~30% of total care costs. Being a high-cost user was associated with older age (>80 years), facing financial difficulties and poor experiences of home care, but not with having cancer or multimorbidity. Palliative care services consistently had the highest satisfaction. Conclusion: Poverty and poor home care drove high costs, suggesting that improving community palliative care may improve care value, especially as palliative care expenditure was low. Major diagnostic variables were not cost drivers. Care costs in the United States were high and highly variable, suggesting that high-cost low-value care may be prevalent.